N-3 (Omega-3) Polyunsaturated Fatty Acids in the Pathophysiology and Treatment of Depression: Pre-clinical Evidence - Levant, Beth (2013)
A growing literature suggests the association of low tissue levels and/or dietary intake of n-polyunsaturated fatty acids (PUFA) with depressive illnesses. Animal studies show that low tissue and/or dietary n-3 PUFAs can lead to behaviors and neurobiological effects associated with depression, and can potentiate the consequences of stress. Higher n- 3 PUFA tissue levels or intake have the opposite effect. These data support the involvement of n-3 PUFAs levels in the disease processes underlying depression. In addition, these pre-clinical findings indicate neurobiological mechanisms whereby n-3 PUFAs may contribute to the disease including control of serotonergic and dopaminergic function, modulation of brain-derived neurotrophic factor (BDNF) in the hippocampus, regulation of the hypothalamic-pituitary-adrenal axis, and effects on neuroinflammation. This pre-clinical evidence for a role for n-3 PUFA in the pathophysiology and treatment of depressive illness are reviewed. The implications of these finding for future pre-clinical research and clinical application are discussed.